The only constant in HRM today is change - Stone, Dianna L., 1947-; Dulebohn, James H. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
In this issue of Research Human Resource Management we consider some of the challenges facing organizations today including changes in the population, the increased competition for talent, and the rise in the use of technology. The issue also includes a number of thought-provoking articles that describe strategies for developing sound theories in our field, discuss the consequences of growing diversity in organizations, consider the factors affecting the success of virtual teams, present methods for increasing emotion control for incumbents in emotionally laden jobs, and discuss leadership and performance management in virtual teams.The first article in this issue compares prospect theory to goal setting theory, and highlights the critical elements needed for theory development in our field. A second article reviewed the literature published from 1976 to 2017 in the Academy of Management Review, the primary theoretical journal in management, and identified the factors associated with the most effective theories published over the last forty years. In view of the growing diversity in organizations, the next article provided a ranking of individual attributes that might be viewed as stigmatizing in organizations. The findings revealed that blemishes of character (e.g., criminality, drug addiction) were viewed as most stigmatizing followed by abominations of the body (e.g., paralysis, leg amputation), and the least stigmatizing attributes were tribal stigmas (e.g., ethnicity, religion). The fourth article focuses on a similar topic, and presents an interesting model of the factors thought to influence weight-based bias. Both of these articles have important implications for overcoming unfair discrimination and increasing the inclusion of all individuals in organizations.The next article offers an input-throughput-output model of virtual teams, and reviews the literature on each of the variables thought to influence the success of these teams. Given that many customer service jobs in the new economy involve high levels of emotional labor, the sixth article reviews the strategies that can be used to train employees on emotion regulation in these challenging jobs. The final article suggests that leadership and performance management should be aligned with the new team-centric structure of organizations in order to enhance team and organizational performance. In particular, they maintained that organizations need to adopt positive and relational leadership, and redesign performance appraisals to support the new team processes. They also recommended that organizations discontinue the use of forced distribution performance ranking systems. We are confident that these articles will inspire new ideas among researchers in our field, and foster additional theory and research on these important topics.
Keywords: Personnel management.; Organizational change.; Personnel management -- Technological innovations.; Business & Economics -- Human Resources & Personnel Management.; Personnel and human resources management.; elektronické knihy; electronic books